Professor Fernando Costa— A Man Ahead of His Time - Isolan, Gustavo Rassier (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
This article describes the milestones in the life Brazil’s greatest neurosurgeons, Professor Fernando Costa. Born and raised in the city of Pelotas, RS, Professor Fernando was an exemplary doctor. As former director and professor at the Catholic University of Pelotas, School of Medicine, his courage as well as his ethical attitude and transparency were the central traits of this masterful teacher. He will be eternally remembered as a great physician, teacher, father, husband, grandfather and friend.
Keywords: Fernando Costa; Universidade Católica de Pelotas; school of medicine; neurosurgery; professor